2017
DOI: 10.1039/c7ra11640c
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and current–voltage characteristics of flexible Ag/BaTiO3 nanocomposite films processed at near room temperature

Abstract: High dielectric constant ceramic-polymer composite materials have been produced by thermal-treatment in the range of 160 to 200 C. Here, we introduce a room temperature process of generating flexible high dielectric constant nanocomposite films on a polymer substrate by combining a printing technique with a UV-curing process. The composite structure is based on nanoscale BaTiO 3 and Ag particles dispersed in a UV-cured polymer matrix. Dielectric characteristics of the nanocomposite thick films depended on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Photopolymerization and UV curing represent fast and solvent-free techniques to obtain polymer-based composites, being two of the effective methods used in the polymerization process. Up to now, just a few studies on UV-curable dielectric materials have been reported, mainly focusing on their electrical properties [ 70 , 71 ]. Later, Mendes-Felipe et al provided further characterization on the morphological, thermal, mechanical, and dielectric properties of BaTiO 3 /PUA composites as a function of the particle content and size [ 72 ].…”
Section: Process and Architecture Of Bidirectional Sensormentioning
confidence: 99%
“…Photopolymerization and UV curing represent fast and solvent-free techniques to obtain polymer-based composites, being two of the effective methods used in the polymerization process. Up to now, just a few studies on UV-curable dielectric materials have been reported, mainly focusing on their electrical properties [ 70 , 71 ]. Later, Mendes-Felipe et al provided further characterization on the morphological, thermal, mechanical, and dielectric properties of BaTiO 3 /PUA composites as a function of the particle content and size [ 72 ].…”
Section: Process and Architecture Of Bidirectional Sensormentioning
confidence: 99%
“…Up to now, just a few studies on UV curable dielectric materials have been reported, mainly focussing on the electrical properties of the materials. Among them, polyethylene glycol diacrylate composites with BaTiO3 particles with two different sizes and filler concentrations up to 50 wt% has been developed [27], as well as composites based on UV-curable resin Loctite® with Ag and BaTiO3 nanoparticle content up to 56.2 vol% [35], leading to films with dielectric constants between 25 and 300, depending the filler size and concentration. It is to notice that relevant parameters such as mechanical ones or in.depth theoretical modelling/interpretation of the observed behaviours have not been reported for these or related systems.…”
Section: Introductionmentioning
confidence: 99%
“…As a best result, a dielectric constant of ~300 and a dielectric loss of 0.08 were achieved when 81 nm BaTiO 3 and 34 nm Ag particles were used at 56.2% overall integrals, which is very competitive for flexible capacitor devices. The current-voltage behavior of nanocomposite films largely depends on the Ag content associated with conductive osmotic transition [4]. Nanocomposite thick film electrodes have been investigated for use in highly integrated microcircuit devices requiring delayed densification to match potential co-fired ceramic sheets.…”
Section: Introductionmentioning
confidence: 99%